Geðlyfjaávísanir utan sjúkrahúsa í Reykjavík í mars 1984 - Tómas Helgason; Júlíus K. Björnsson (Læknafélag Íslands, Læknafélag Reykjavíkur, 2010)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn Skoða/Opna(view/open) All prescriptions for psychotropic drugs, paid by the Sick Benefit Association in Reykjavik, during a one month period in 1984 were analyzed by: type of drug prescribed, the sex and age distribution of the patients, quantity prescribed, mode and frequency of prescription. Each patient obtained on an average 1.3 prescriptions containing 1.7 different types of drugs. About 83% of the prescriptions were for tranquillizers and hypnotics. Almost one half of the prescriptions contained other drugs as well. Over 40% of the prescriptions were given by telephone. About 4% of the patients were prescribed more than 90 Daily Defined Doses (DDDs) of tranquillizers during one month and 10% of the patients were prescribed an equivalent quantity of hypnotics. The prevalence of psychotropic drug prescriptions during one month was 5.3% for men and 8.6% for women aged 15 years and over. The prevalence rate increased by increasing age especially for hypnotics. The prevalence figures are approximately 60% of the number of DDDs prescribed during this month. The latter figures are similar to those found in 1974 except for anxiolytic drugs which have decreased markedly. A recent Gallup survey indicates that the prevalence of use of tranquillizers and hypnotics has not changed since 1984. Two thirds of the prescriptions were for women and approximately one third for people aged 65 or more. Geðlyfjaávísanir, sem Sjúkrasamlag Reykjavíkur greiddi í mars 1984, voru athugaöar til að kanna kyn- og aldursdreifingu sjúklinganna og hvaða tegundum geðlyfja læknar ávísuðu, hve miklu þeir ávísuðu hverjum sjúklingi og hve oft og hvernig. Niðurstöðurnar eru bornar saman við fyrri athugun (1, 2) og við sölutölur geðlyfja á landinu (3). Hver sjúklingur fékk að meðaltali 1,3 lyfseðla á mánuði og að jafnaði var ávísað 1,7 mismunandi geðlyfjum. Um 83% ávísana voru á svefnlyf eöa róandi lyf. Á tæpum helmingi lyfseðlanna var öðrum lyfjum ávísað ...